Coronavirus disease 2019: achieving good mental health during social isolation. (August 2020) - Diamond, Rowan; Willan, John
Summary: The coronavirus disease 2019 pandemic has led to unprecedented disruption to the normal way of life for people around the globe. Social distancing, self-isolation or shielding have been strongly advised or mandated in most countries. We suggest evidence-based ways that people can maintain or even strengthen their mental health during this crisis.